Clinical features of treatment-naive patients with hepatitis B virus infection: A community-based survey from high- and intermediate-hepatitis B endemicity regions in Southeast China. Issue 16 (April 2017) - Wu, Wei; Zhu, Yu; Yu, Chenbo; Yang, Shigui; Ruan, Bing; Chen, Yu; Li, Lanjuan
Abstract : Abstract: The aim of study was to investigate the clinical features of treatment-naive patients in 2 regions with high- and intermediate-hepatitis B endemicity level in Southeast China and provide the baseline data for monitoring health or planning therapy. This study included 8207 cases of treatment-naive patients with hepatitis B virus (HBV) infection from Yuhuan (YH, high-hepatitis B endemicity region) and Shaoxing (SX, intermediate-hepatitis B endemicity region) during 2014–2015. Clinical data were collected from the patients. Blood samples were kept for detecting hepatitis B surface antigen, hepatitis B envelope antigen (HBeAg), hepatitis B envelope antibody, hepatitis B surface antibody, hepatitis B core antibody, liver function, HBV deoxyribonucleic acid, and alpha-fetoprotein. All persons underwent B ultrasound to exclude liver cirrhosis or cancer. Of all 8207 HBsAg-positive patients, 52.9% patients were in the low-replication (LR) stage and 30.3% in the HBeAg-negative chronic hepatitis B (ENH) stage; 8.8% cases were in the ENH stage with elevated alanine aminotransferase (ALT). More male than female patients were in immune clearance (IC) or ENH stages with elevated ALT (10.4% vs 4.8%, 12.1% vs 5.3%, respectively, P < .05). The percentage of patients in IC and immune tolerant (IT) stages declined with increasing age, whereas the percentages of ENH with elevated ALT stage were highest in 40 to 60 years. The percentage of patients in IT and IC stages was higher in YH than in SX (9.4% vs 3.8%, 9.9% vs 4.2%, respectively, P < .05). More patients had HBVDNA≥10 5 IU/mL in YH than in SX (24.6% vs 16.0%, P < .05), and more male than female patients had HBVDNA≥10 5 IU/mL(24.5% vs 17.9%, P < .05). Clinical features varied in treatment-naive patients with HBV infection between different genders and regions. More attention should be paid to the surveillance and therapy of patients in YH especially male patients for the prevention and prognosis of hepatitis B. Abstract : Supplemental Digital Content is available in the text